Hepatorenal Syndrome: A Way for Early and Accurate Diagnosis - Aboul-Ezz, Mohammad A.; Rahim, Ali Abdel; El-Mikkawy, Ahmed; Elkady, Mohammad A.; Elrefaiy, Mohamed. A; El-Shishtawy, Samia; Mosbah, Osama; Mabrouk, Khaled; Elshafie, Mostafa; Sabry, Omar M. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Hepatorenal syndrome (HRS) is a devastating consequence of liver cirrhosis that is clinically categorized into two subtypes. Acute malfunction of renal role, as measured by an elevation in blood creatinine, significantly underestimates the loss in renal function in cirrhotic individuals; more accurate biomarkers are desperately required in cirrhotic patients. AIM: The present study set out to uncover new biomarkers for the early prediction of AKI in cirrhotic cases. A comprehensive panel of biomarkers was investigated to get a clear insight into the pathogenesis of HRS. PATIENTS AND METHODS: Participants in this study were 70 individuals from the hepatogastroenterology unit of the Theodor Bilharz Research Institute (TBRI). Detailed medical data and a physical examination were recorded. Three groups of patients have been identified; Group 1: 30 cases with compensated liver cirrhosis and normal kidney functions. Group 2: 20 cases with decompensated liver cirrhosis and normal kidney functions. Group 3: 20 cases with decompensated liver cirrhosis proved hepatorenal syndrome Type 2 h. The following biomarkers were detected in serum using the sandwich-ELISA method: Human L-arginine ELISA kit, human neutrophil gelatinase related lipocalin (NGAL), human noradrenaline (NA), human asymmetrical dimethylarginine (ADMA), human symmetric dimethylarginine (SDMA), human nitric oxide (NO), and human renin. RESULTS: There was a highly significant difference between Groups 1 and 2 in NITRIC and ADMA. Significant differences between Groups 2 and 3 in NGAL, noradrenalin, and SDMA were observed. There was a significant difference (Group 2 vs. Group 3) in renin, NITRIC, ADMA, and L-ARGININE. There was highly significant differentiation (Group 2 vs. Group 3) in NGAL, noradrenalin, and SDMA. There was highly significant variation as per odd ratio and confidence interval between (Group 3 vs. Group 2) in NGAL. CONCLUSION: Assessment of renal biomarkers in individuals with decompensated cirrhosis gives critical information on the etiology of AKI. Further, it may aid in the diagnosis and prognosis of AKI. Renin, NITRIC, ADMA, and L-ARGININE could be used as biomarkers to indicate HRS in individuals with advanced cirrhosis.